ASASSN-18tb: a most unusual Type Ia supernova observed by TESS and SALT. Issue 2 (27th May 2019) - Vallely, P J; Fausnaugh, M; Jha, S W; Tucker, M A; Eweis, Y; Shappee, B J; Kochanek, C S; Stanek, K Z; Chen, Ping; Dong, Subo; Prieto, J L; Sukhbold, T; et al.
ABSTRACT: We present photometric and spectroscopic observations of the unusual Type Ia supernova ASASSN-18tb, including a series of Southern African Large Telescope spectra obtained over the course of nearly six months and the first observations of a supernova by the Transiting Exoplanet Survey Satellite . We confirm a previous observation by Kollmeier et al. showing that ASASSN-18tb is the first relatively normal Type Ia supernova to exhibit clear broad (∼1000 km s −1 ) H α emission in its nebular-phase spectra. We find that this event is best explained as a sub-Chandrasekhar mass explosion producing$M_{ Ni} ≈ 0.3\, \, \rm {M}_\odot$ . Despite the strong H α signature at late times, we find that the early rise of the supernova shows no evidence for deviations from a single-component power-law and is best fit with a moderately shallow power law of index 1.69 ± 0.04. We find that the H α luminosity remains approximately constant after its initial detection at phase +37 d, and that the H α velocity evolution does not trace that of the Fe iii λ4660 emission. These suggest that the H α emission arises from a circumstellar medium (CSM) rather than swept-up material from a non-degenerate companion. However, ASASSN-18tb is strikingly different from other known CSM-interacting Type Ia supernovae in a number of significant ways. Those objects typically show an H α luminosity two orders of magnitude higher than what is seen in ASASSN-18tb, pushing them away from the empirical light-curve relations that define 'normal' Type Ia supernovae. Conversely, ASASSN-18tb exhibits a fairly typical light curve and luminosity for an underluminous or transitional SN Ia, with MR ≈ −18.1 mag. Moreover, ASASSN-18tb is the only SN Ia showing H α from CSM interaction to be discovered in an early-type galaxy.